Comparative Evaluation of Two Different Bolus Doses of Nor-epinephrine to Prevent Post Spinal Hypotension in Patients Undergoing LSCS - Renu Wakhloo; Anjali Mehta; Aqiba Afzal (Dr. Annil Mahajan, 2021)
Background: Until now phenylephrine has been the first choice for prevention and treatment of spinal anaesthesia for LSCS; however serious bradycardia caused by phenylephrine was of great concern. Purpose: To evaluate the effectiveness of 2 different bolus doses of nor-epinephrine for prevention of hypotension during spinal anaesthesia while reducing the incidence of bradycardia caused by phenylephrine. Material and Methods: A total of 60 patients undergoing LSCS under spinal anaesthesia were enrolled in the randomised double-blind study to receive either prophylactic nor-epinephrine bolus 10 mcg (group A) or 15 mcg (group B) immediately after spinal anaesthesia. Results: Only one patient in both the groups had bradycardia which was corrected by Inj. Atropine 0.3mg i.v stat and only 1 patient in group A developed hypotension requiring a rescue dose of vasopressor, mephentremine. 3 patients in group B developed systolic hypertension (the difference being statistically significant) which settled without requiring intervention. Conclusion: Both 10 &15 mcg of norepinephrine were effective in preventing hypotension, the dose of 15 mcg did not have any added advantage. A bolus dose of 10 mcg of Norepinephrine proved to be a good preventive measure against hypotension with reduced incidence of adverse effects.